Experimental Evolution Reveals Redox State Modulates Mycobacterial Pathogenicity - Jiang, Zheng; Zhuang, Zengfang; Mi, Kaixia (Frontiers in Genetics, 2022)
Understanding how Mycobacterium tuberculosis evolved into a professional pathogen is helpful for studying its pathogenesis and design vaccine. We showed that the evolutionary adaptation of M. smegmatis mc251 to an important clinical stressor H2O2 made the bacteria to undergo coordinated genetic change, which results in increasing pathogenicity. Whole-genome sequencing showed that the mutation site was in fur, and the mutated Fur increased the katG level. In the Wayne dormancy model, mc251 showed a growth advantage over its parental strain mc2155 in recovering from dormancy under anaerobic conditions. Meawhile, the high level of KatG in mc251 is accompanied by low level of ATP, which means that mc251 is at a low respiratory level. In addition, we showed that the redox-related protein Rv1996 exhibits different phenotypes in different specific redox states in M. smegmatis mc2155, mc251 and M.bovis BCG. This study shows that the same genotype presents different phenotypes under different physiological conditions. We, at least partly, explain why M. smegmatis and M. tuberculosis have similar virulence factors, two component systems and sigma factors, but the former is a non-pathogen and the latter is a pathogen. Our results show that H2O2 -resistant M. smegmatis mc251 can evade host defense and manifest defined pathogenicity in mice and the H2O2 resistant mutant mc251 can be potentially developed as a vaccine vector.